Konsep Pendidikan Moderasi Beragama Hamka untuk Wujudkan Toleransi Antar Umat Beragama - Sri Wahyuna; Heru Gunawan (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to identify and analyze Buya Hamka's perspective on religious moderation in realizing interfaith tolerance in Indonesia. The type of research used by the researcher is library research, which focuses on library results, or research that utilizes libraries to obtain research data. This study employs content analysis, a technique that uses a set of procedures to draw valid conclusions from a book or document through induction. Based on the results of the research, the background to Buya Hamka's formulation of the concept of religious moderation cannot be separated from the social context surrounding him, such as the Indonesian mindset and the heterogeneous environment, as well as the environment of the Muhammadiyah organization. However, all of Buya Hamka's thoughts on the concept of religious moderation remain grounded in the main pillars, namely the Qur'an and the Sunnah. Buya Hamka's thoughts on the concept of religious moderation are balance, consistency, justice, and tolerance. From this, people will come to understand and respect one another, as Islam teaches not only to maintain a good relationship with Allah but also to maintain a good relationship with fellow human beings. Moreover, in Islam, religious rituals always produce outcomes that foster peace and love among one another. Thus, the ultimate goal of Buya Hamka's religious moderation is happiness and peace among people of different faiths. The practical steps that can be taken to achieve Buya Hamka's concept of religious moderation are to include the material in formal education, hold seminars or talk shows, support content creators who promote diversity, and create a platform for religious moderation. since millennials are often active on social media, the ultimate goal of religious moderation the love of peace can be felt amidst existing differences.